Analisis Kemandirian Keuangan Daerah Kabupaten Belu - Kamilaus Konstanse Oki; Frederic W Nalle; Pricilia A.V Meomanu (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2020)
Belu Regency located in the border region of Indonesia and Timor Leste has economic and political strategic value. Since 2001 the central government has been granted the right to autonomy in managing regional development. Regional finance is the main factor for the government in financing regional needs. The financial resources of the Belu district as regulated in the law are the original regional revenue, the balance fund, profit sharing and other legal income. The financial capacity of the Belu district as measured by fiscal capacity is very small on average 7.81 percent. The level of dependency on the central government is very high, on average, 84.29 percent. This was confirmed by the financial independence of the Belu district which was very low, averaging 8.08 percent and included in the instructive category, meaning that the role of the central government was more dominant than the independence of the regional government.